Effect of imposing changes in kick frequency on kinematics during undulatory underwater swimming at maximal effort in male swimmers - Shimojo, H.; Sengoku, Y.; Miyoshi, T.; Tsubakimoto, S.; Takagi, H. (Human Movement Science, 2014)
Undulatory underwater swimming (UUS) is an important swimming technique after a start and after turns. It was considered that a higher swimming velocity (U) resulted from a higher kick frequency (f), and greater propelling efficiency, i.e., Strouhal number (St) and Froude efficiency (nF), resulted from a lower f. The aim of this study was to investigate whether changing f affected U and St, nF plus other kinematics of UUS. Ten national-level male swimmers participated in the study. First, the swimmers performed maximal UUS (Pre; this f was defined as 100% F). Second, the swimmers synchronized their f with the sound of a metronome and with six frequencies (85% F, 90% F, 95% F, 105% F, 110% F, and 115% F) randomly presented. During the higher f sessions, kick amplitude (A) significantly decreased from Pre (115% F: -10.8%, p < .05); however, U was unchanged. In contrast, in lower f sessions, St and nF were unchanged, but the wavelength per body length , which indicates UUS mode, significantly decreased (90% F: -1.3%, p < .05). In conclusion, these results suggest that increasing f for UUS would not affect U, but a decrease in f may be suitable for human undulation training.